Remaining in rural areas: towards a rural entrepreneur’s analysis framework - Ramirez Gomez, Carlos Julian; Cuevas Reyes, Venancio; Morris, Wyn (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
This research employs an empirical approach to understand aspects defining why young people remain in their rural territories. Utilising a rural region of Caldas, Colombia as a case study and based on an agricultural education program for entrepreneurship, information from 368 rural young people was obtained. The study explored a conceptual model shaped by four dimensions and 34 variables. Using a Probit method, we identify significant variables regarding permanence in rural areas. We identify 11 key variables that determine the categories of socio-demographic profile, profile of entrepreneur characteristics, and category of motivations and territory. Our study contributes to literature on rural entrepreneurship from an empirical approach. Additionally, we propose a new analytical framework to address major problems in agriculture and rural territories, particularly in developing countries, such as Latin America. Highlights: This paper proposes an analysis model of the rural entrepreneur, which seeks to understand the aspects that determine the interest of rural young people wanting to stay within their own rural territories. The categories and variables determining the permanence of rural youth in their territory based on entrepreneurship can be divided into an internal environment such as the dimensions of the profile and skills for entrepreneurship, as well as an external environment based on what determines the territory as a motivational factor. The model shows the relevance of the interrelation of dimensions and environments, as even when rural young people have entrepreneurial skills, there are other aspects that promote permanence in the territories.